Bilateral adrenal haematoma complicated by adrenal insufficiency in a patient treated with bevacizumab. Issue 2 (22nd February 2021) - Smolenschi, Cristina; Tazdait, Melodie; Kuhn, Emanuelle; Boige, Valerie
Abstract : Bevacizumab (bev) significantly improves outcomes of patients with metastatic colorectal cancer (mCRC). However, the addition of bev to concurrent chemotherapy significantly increased the risk of haemorrhage. We describe the case of a patient with mCRC who presented with acute diffuse abdominal pain following four cycles of bev-containing systemic chemotherapy. A CT revealed the appearance of bilateral adrenal enlargement suggestive of acute adrenal haematoma. Blood test results showed a dramatic decrease in cortisol level and highly elevated Adrenocorticotropic Hormone (ACTH) level suggesting an adrenal insufficiency. After differential diagnosis, we hypothesised that bev may have contributed to the development of a bilateral adrenal haematoma complicated by adrenal insufficiency. Bev was immediately withdrawn and the patient was subsequently treated with hydrocortisone substitution with favourable outcome. This case highlights for the first time the possibility of adrenal bleeding with bev-containing chemotherapy.